Pharmacologic Blockade of 15-PGDH Protects Against Acute Renal Injury Induced by LPS in Mice - Miao, Shuying; Lv, Caihong; Liu, Ying; Zhao, Jie; Li, Ting; Wang, Chunjiang; Xu, Yunfei; Wang, Xiaoli; Xiao, Xianzhong; Zhang, Huali (Frontiers in Physiology, 2020)
Prostaglandin pathway plays multiple roles in various physiological and pathological conditions. The present study aimed to investigate the effect of 15-hydroxyprostaglandin dehydrogenase (15-PGDH), a key enzyme in the degradation of prostaglandins, on lipopolysaccharide(LPS) induced-acute kidney injury (AKI) in mice. In this study, male C57BL/6J mice were injected intraperitoneally with LPS(10mg/kg). SW033291, a potent small-molecule inhibitor of 15-PGDH, was used to investigate the therapeutic potential of 15-PGDH inhibition on LPS-induced AKI. We discovered that the expression of 15-PGDH protein was up-regulated in kidneys of LPS-stimulated mice, and it was mainly localized in the cytoplasm of renal tubular epithelial cells in renal cortex and outer medulla. SW033291 administration improved the survival rate of mice, and attenuated renal injury of mice that were challenged by LPS. Additionally, inhibition of 15-PGDH also reversed LPS-induced apoptosis of renal cells, increased expression of anti-apoptotic protein Bcl-2, and downregulated expression of Fas, Caspase-3 and Caspase-8. Pretreatment of SW033291 enhanced autophagy in kidney cells after LPS stimulation. Our data also showed that inhibition of 15-PGDH relieved the level of lipid peroxidation and downregulated NADPH oxidase subunits induced by LPS in mice kidneys, but had no significant effect on the release of inflammatory factors, such as IL-6, IL-1β, TNF-α and MCP-1. Our study demonstrated that inhibition of 15-PGDH could alleviate LPS-induced AKI by regulating the apoptosis, autophagy, and oxidative stress rather than inflammation in mice.